Influence of exercise duration on serum insulin-like growth factor and its binding proteins in athletes - Nguyen, U. N.; Mougin, F.; Simon-Rigaud, M. L.; Rouillon, J. D.; Marguet, P.; Regnard, J. (European Journal of Applied Physiology, 1998)
From our results it would appear that [IGFBP-1] increase to bind free IGF and hinder their insulin-like action during long-term exercise (lasting beyond 45 min). It is suggested that IGFBP-1 might thus contribute both to preventing hypoglycaemic action of IGF and to facilitating glucose uptake by muscle cells when muscle glycogen stores become deplete.